Quality and sensory characteristics of pan de sal produced from wheat and soybean flour blends - Alcaraz, Ma. Clarizze M.; Francisco, Ma. Leonora de Leon (Quezon City College of Home Economics, University of the Philippines Diliman, 2014)
All-purpose wheat flour was supplemented with defatted soybean flour at levels of 0%, 5%, 10%, and 15%. The blends were applied to the pan de sal recipe and procedure by Luna (2007). Sensory test showed that the supplementation had significant effects on some sensory parameters in the analysis. Color of the bread became more intense and its contour became more round with increasing soybean flour level. It was also known that minimal differences were observed in the soy odor and flavor of the samples attributed to the non-familiarity of the panelists to the characteristics of soy flour. However, overall acceptability explained that supplementation can be done up to 15% since no significant difference was found. For the Kjeldahl analysis, the crude protein content of pan de sal increased from 7.66% to 12.74% with the increase in the level of substitution. Photocopied cross-sections of the samples exhibited that there was a decreasing trend in the size of the bread and air cells as the concentration of soy flour increases. Photographs showed that there was evident modification in the color and size of the samples. Objective tests also indicated that the height, width, volume and specific volume of the samples had indirect relationships with the increasing level of soybean flour substitution. Overall, the study implied that the substitution is acceptable based on sensory test, soybean flour can increase the protein content and can decrease the physical characteristics of pan de sal. Therefore, it is suggested to utilize dough improvers to alleviate the changes in its physical characteristics.
Thesis Classification: F
Thesis (B.S. in Food Technology)--University of the Philippines Diliman
Includes bibliographical references and appendices.
Keywords: Bread -- Philippines; Soy flour -- Philippines; Wheat flour -- Philippines